2020
DOI: 10.1038/s41598-020-66292-3
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol restores autophagy flux in bafilomycin A1-treated, cultured cortical astrocytes through lysosomal reacidification: roles of PKA, zinc and metallothionein 3

Abstract: Cilostazol, a phosphodiesterase 3 inhibitor, reduces the amyloid-beta (Aβ) burden in mouse models of Alzheimer disease by as yet unidentified mechanisms. In the present study, we examined the possibility that cilostazol ameliorates lysosomal dysfunction. Astrocytes treated with bafilomycin A1 (BafA1) exhibited markedly reduced DND-189 and acridine orange (AO) fluorescence, indicating reduced lysosomal acidity. In both cases, BafA1-induced alkalization was reversed by addition of cilostazol, dibutyryl cAMP or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In our previous studies, we have demonstrated that increasing cAMP concentrations can markedly restore lysosomal acidity even in astrocytes treated with bafilomycin A1 (BafA1), a potent and selective v‐ATPase inhibitor (Kim, Seo, Kim, & Koh, 2020; Koh, Kim, Hwang, Kim, & Park, 2019). Considering that lysosomal free zinc levels increase concurrently with cAMP treatment in a TPEN‐dependent manner, it may be possible that proton pumps other than v‐ATPase, acting in concert with certain zinc transporters, may contribute to the regulation of lysosomal pH in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have demonstrated that increasing cAMP concentrations can markedly restore lysosomal acidity even in astrocytes treated with bafilomycin A1 (BafA1), a potent and selective v‐ATPase inhibitor (Kim, Seo, Kim, & Koh, 2020; Koh, Kim, Hwang, Kim, & Park, 2019). Considering that lysosomal free zinc levels increase concurrently with cAMP treatment in a TPEN‐dependent manner, it may be possible that proton pumps other than v‐ATPase, acting in concert with certain zinc transporters, may contribute to the regulation of lysosomal pH in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…NCAM, sVCAM-1, and cathepsin D were uniquely elevated in hNSC-treated animals when compared to vehicle controls. This could be related to an enriched population of stem cells, as NCAM and sVCAM-1 are known to be related to neural stem cell survival, proliferation, and migration ( Shan, 2013 ; Klein et al, 2016 ), whereas increases in the protease cathepsin D are associated with improved amyloid beta clearance ( Gao et al, 2020 ; Kim et al, 2020 ). This effect could also be related to hNSC secretion of IGF-1, shown to promote survival of NCAM-expressing neural progenitors ( Gago et al, 2003 ; Monzo et al, 2013 ), which can mediate and induce cathepsin D expression ( Cappelletti et al, 1996 ; Wang et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clioquinol, a zinc ionophore, induces autophagy in a zinc-dependent manner and contributes to the clearance of aggregated proteins in astrocytes and neurons ( Park et al, 2011 ). The addition of cilostazol, a phosphodiesterase (PDE) inhibitor, was found to restore autophagic flux blocked by bafilomycin A1 via lysosomal re-acidification in a zinc-dependent manner ( Kim et al, 2020 ). Koh et al also showed that the H + /K + -ATPase/ZnT3 complex is recruited to lysosomes in a cAMP-dependent manner and functions as an alternative proton pump for lysosomes when the V-ATPase function is downregulated by bafilomycin A1 ( Lee and Koh, 2021 ).…”
Section: Introductionmentioning
confidence: 99%